Anonymous
Anonymous asked in Science & MathematicsMathematics · 1 month ago

solve the following system by the addition method: 4x + 2y =-2; -4x -9y =23?

Update:

Please..really confused with this stuff.

8 Answers

Relevance
  • 1 month ago
    Favourite answer

    4x-2y=-2

    -4x-9y=23

    add left sides; -7y=

    add right sides; =21

    divide y=21/-7=-3>>y=-3

    4x-2(-3)=-2>> 4x-6=-2>>4x=-2+6=4>>x=1

    check them in original equations.

    4(1)-2(-3)=-2

    -4(1) -9(-3)=23>>-4+27=23

    Practice these, they are fun when you learn how.

  • 1 month ago

    Simultaneous Equations 

    Add the two equ'ns , this will eliminate 'x'.

    -7y = 21 

    y = -3 

    When y = -3 

    4x + 2(-3) = -2 

    4x - 6 = -2 

    4x = 4 

    x = 1 

    Hence the answer in (x,y) form is ( 1, -3) 

  • 1 month ago

    (1) : 4x + 2y = - 2

    (2) : - 4x - 9y = 23

    You calculate (1) + (2)

    (4x + 2y) + (- 4x - 9y) = - 2 + 23

    4x + 2y - 4x - 9y = 21

    - 7y = 21

    → y = - 3

    Recall (1) : 4x + 2y = - 2

    4x = - 2 - 2y → we've just seen that: y = - 3

    4x = - 2 + 6

    4x = 4

    → x = 1

    ---------------------------------------------------------------------------------------------------------------------------------------

  • Philip
    Lv 6
    1 month ago

     4x + 2y = -2...(1).;

    -4x - 9y = 23...(2),;

    [(1)+(2)] ---> -7y = 21, ie., y = -3. Then (1) ---> x = (1/4)(-2-2y) = -(1/2)(y+1) = 1. 

  • What do you think of the answers? You can sign in to give your opinion on the answer.
  • 1 month ago

     4x + 2y = -2

     -4x - 9y = 23

     -7y = 21

     y = -3

     x = 1

     (x, y) = (1, -3)

  • 1 month ago

    4x + 2y = - 2   Add eq1 and eq2 

    -4x - 9y = 23

    ----------------------

     -7y = 21

      y = -3

    solving for x from eq1 by plugging in y = - 3.

    4x + 2y = - 2

    4x + 2(-3) = - 2

    4x  - 6  = - 2

    4x = - 2 + 6

    4x = 4

     x = 1

    The x and y values are: (1,- 3)............ Answer//

  • 1 month ago

    4x + 2y = -2

    -4x - 9y = 23

    ----------------

    ......-7y = 21

    y = -3

    4x + 2(-3) = -2

    4x - 6 = -2

    4x = 4

    x = 1

  • alex
    Lv 7
    1 month ago

    by the addition method---> -7y = 21

    solve for y 

    then find x

Still have questions? Get answers by asking now.